MANAJEMEN PERENCANAAN PENDIDIKAN ISLAM (Kajian Tematik Al-QurÃ¢â¬â¢an dan Hadist) - Ikhwan, Afiful (EDUKASI: Jurnal Pendidikan Islam, 2016)
Educational planning is closely associated with the structure of society, there are three approaches in planning, namely: social needs approach, the approach of labor, cost effectiveness approach. Planning Education in the Prophets time is divided into two phases, namely the phase of Makkah and Madinah phase. Planning education in Mecca or before the hijrah was superior in the field of faith and morals in accordance with Islamic values. Planning education in Madinah or after the Hijra was superior in the areas of religious, moral, social, economic, and social, as well as its application in life. Planning and management in the field of Islamic education is difficult to separate from one another. Planning can be seen as a management function, so it is closely related to other functions: organizing, coordinating, monitoring, and assessment. Islamic education planning must be implemented by executing management functions in accordance with such functions.